Beyond The Digital Panopticon: Reclaiming Humanity in Cybersecurity through Noetic-Tech Triumvirate (Data Dignity, Digital Conscience, and Digital Veracity) - Kelik Wardiono (Universitas Muhammadiyah Surakarta, 2026)
Contemporary cybersecurity governance not only traps global citizens within the structure of a Digital Panopticon, but also triggers a deeper existential crisis: the loss of essential human consciousness. Amidst state and corporate surveillance that erodes fundamental rights through the authoritarianism of algorithms, humans are slowly being reduced to mere data commodities, stripped of their human autonomy. By deconstructing the framework of secular legal positivism, this paper conducts an operation of demystification on the text and context of cyberspace. As an antithesis, the paradigm of Noetic Law is proposed through the conceptual framework of the